A Study on Wear Testing of Orthopedic Implant Materials in Simulated Body Fluid - Atar, Erdem (Carl Hanser Verlag, 2013)
In this study, the sliding wear behaviour of the materials utilized in manufacturing of load-bearing orthopedic implants (316 L, T16Al4V, and CoCrMo nickel alloys) was examined by a reciprocating wear tester under ceramic-on-metal configuration in a simulated body fluid (SBF). During the tests the generated wear debris were transferred into the SBF and increased its optical density. In accordance with its poor wear resistance, Ti6Al4V alloy provided a large amount of wear debris transfer into the SBF along with the heavy material attachment to the contact surface of the counterface. Dissolution of wear debris led to an increase of the metal ion concentration in the SBFs. Even though few wear debris were generated, trace elements were detected in the SBFs of the 316 L and CoCrMo alloy, besides the main elements.
Keywords: Metal-Ion Release; Surface Modification; Thermal-Oxidation; Titanium-Alloys; On-Metal; Corrosion; Resistance; Prostheses; Behavior